Improving Quality of Wind Tunnel Test Data Through the MDOE. (2015) - Jiang, Zhang; Handong, Ma; Yongming, Qin
Abstract: Researching on the improvement of the wind tunnel data quality through Modern Design Of Experiments (MDOE) was carried out. A body with fin model was tested in wind tunnel through the MDOE and traditional OFAT (One Factor at A Time) methods. The uncertainties of data from these two different methods were analyzed, and mechanism of defense against systematic error of Randomization and Repetition in the MDOE method was studied. The defense abilities against the time various systematic errors in wind tunnel tests of the MDOE and the OFAT method were compared, and the mean to improve test data quality using repetition principle in the MDOE was studied with the increasing of cost. Main conclusions: The MDOE method can test and eliminate the time various systematic errors during the wind tunnel tests, while the OFAT test data were polluted by the time various systematic errors; The independent variable changes sequently in the OFAT tests, so the test data are not statistically independent. It is the reason of the disability of the defense against the time various systematic errors in OFAT tests. Randomization can transform the systematic errors into random errors in MDOE tests, which can be eliminated. Repetition in MDOE tests can improve the quality of test data since the average variance in the predicted response can be reduced by adding sample points, and amount of the measured data are still less than the amount in OFAT tests.